Quantifying muskmelon fruit attributes with A-TEP-based model and machine vision measurement - Li-ying CHANG; San-peng HE; Qian LIU; Jia-lin XIANG; Dan-feng HUANG (Journal of Integrative Agriculture, 2018)
In this study, we established a dynamic morphological model using the accumulated thermal effectiveness and photosynthetic active radiation (PAR) (A-TEP), aiming to explore the relationship between muskmelon (Cucumis melo L.) fruit attributes and environmental factors. Muskmelon surface color was described by parameters of red, green, blue, hue, saturation and brightness (HSI). Three characteristic parameters, gray level co-occurrence matrix (GLCM), angular second moment (ASM), entropy, contrast, and the coverage rate were used to describe the process of muskmelon fruit netting formation. ASM was not significant difference during muskmelon fruit growth. The number and deep of netting stripes gradually increased with fruit growth. Coverage rate increased rapidly for 15–30 d after pollination. The vertical and horizontal diameters of muskmelon fruit were followed a logistic curve. And root mean squared errors (RMSE) between the simulated and measured vertical and horizontal diameters were 3.527 and 4.696 mm, respectively. RMSE of red, green, blue, saturation and brightness were 0.999, 2.690, 2.992, 0.033 and 5.51, respectively, and the RMSE for entropy, contrast and coverage rates were 0.077, 0.063 and 0.015, respectively, indicating a well consistent between measured and simulated values.